2021
DOI: 10.3390/children8090804
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides: A Comprehensive Review towards Metabolomics

Abstract: Human milk oligosaccharides (HMOs) are the third most represented component in breast milk. They serve not only as prebiotics but they exert a protective role against some significant neonatal pathologies such as necrotizing enterocolitis. Furthermore, they can program the immune system and consequently reduce allergies and autoimmune diseases’ incidence. HMOs also play a crucial role in brain development and in the gut barrier’s maturation. Moreover, the maternal genetic factors influencing different HMO patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 143 publications
(211 reference statements)
1
29
0
Order By: Relevance
“…This trend is in line with previous results ( 38 ). Multiple interactions between HMOs and the infant gut microbiota and environment have been extensively reviewed previously ( 6 , 34 , 40 ). Research has suggested that 2-FL and 3-FL are negatively correlated ( 38 ), and studies have demonstrated that both 2-FL and 3-FL promote the growth of infant gut symbionts, enhance production of short chain fatty acids, and improve intestinal mobility and epithelial barrier function ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…This trend is in line with previous results ( 38 ). Multiple interactions between HMOs and the infant gut microbiota and environment have been extensively reviewed previously ( 6 , 34 , 40 ). Research has suggested that 2-FL and 3-FL are negatively correlated ( 38 ), and studies have demonstrated that both 2-FL and 3-FL promote the growth of infant gut symbionts, enhance production of short chain fatty acids, and improve intestinal mobility and epithelial barrier function ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…HMO 2′-fucosyllactose has been identified as the most abundant HMO in breast milk [ 82 ]. Breast milk due to its high levels of 2′-fucosyllactose has shown advantages for the infant because of its efficiency to promote an early high Bifidobacteria -dominated GM [ 83 ]. Several experiments conducted on the supplementation of HMO documented beneficial effects on the overall health of an individual, which includes modification of the GM [ 78 , 81 , 84 ], effects on immune development [ 78 , 85 , 86 ], anti-adhesive antimicrobial effects [ 87 ], and brain development [ 88 , 89 ] ( Table 1 ).…”
Section: Classification Of Prebioticsmentioning
confidence: 99%
“…The HMO pattern in human milk is influenced by the maternal phenotype, health, diet, and geographical distribution. 1 The law and mechanism of the variations in the HMO pattern are current important research topics related to HMOs. For example, the secretor (Se) and Lewis (Le) genes encode α1,2fucosyltransferase and α1,3/4-fucosyltransferase, respectively, and the activation and/or inactivation status of these two enzymes generated by the mother's genotype decide the fucosylated HMO pattern to a great extent.…”
mentioning
confidence: 99%
“…For example, the secretor (Se) and Lewis (Le) genes encode α1,2fucosyltransferase and α1,3/4-fucosyltransferase, respectively, and the activation and/or inactivation status of these two enzymes generated by the mother's genotype decide the fucosylated HMO pattern to a great extent. 1 HMOs are indigestible because humans lack the related digestive glycosidases. Instead, the abundant HMOs act as prebiotics to enhance the proliferation of the beneficial microbes and promote the infant intestinal health.…”
mentioning
confidence: 99%
See 1 more Smart Citation